Development of a Mouse Biomagnetic Measurement System by Using a High- T SQUID Magnetometer - Kim, In-Seon; Ahn, San; Lee, Chul-Ho; Lee, Yong-Ho (IEEE transactions on applied superconductivity, 2011)
We have developed a biomagnetic measurement system for mouse by using high-T C SQUID magnetometer. The system consists of a high-T C SQUID magnetometer, a table-top magnetically shielded box, and a nonmagnetic dewar with a warm-to-cool distance of about 4 mm. Mice with weights of about 27 g were anesthetized and fixed in supine position on a plastic xyz-stage inside the shield box. The SQUID readout signal was digitized in 24-bit and recorded with sampling rate of 1280 Hz. We carried out a scanning measurement by changing x- and y-position of the subject inside the shield box. Finally, we could obtain clear mouse MCG waveforms of about 20 pT in peak amplitude with well defined P-, QRS-, and T-wave. We demonstrated the high-T C SQUID magnetometer based biomagnetic measurement system is useful for monitoring mouse MCG signals with sufficient noise-to-signal ratio.